Evaluation of T3B fingerprinting for identification of clinical and environmental Sporothrix species - Oliveira, Manoel Marques Evangelista de (2015)
In this study, PCR fingerprinting using the universal primer T3B was applied to distinguish among clinical and environmental species of the Sporothrix complex, Sporothrix brasiliensis, S. globosa, S. mexicana, S. pallida, S. luriei and S. schenckii sensu stricto. The T3B fingerprinting generated clearly distinct banding patterns, allowing the correct identification of all 43 clinical and environmental isolates at the species level, what was confirmed by partial calmodulin gene sequence analyses. This technique is reproducible and provides the identification of all species of the Sporothrix complex with sufficient accuracy to be applied in clinical mycology laboratories as well as in epidemiological studies in order to obtain a better understanding of the epidemiology of sporotrichosis.